A Translational Turn : Latinx Literature into the Mainstream - Sánchez, Marta Ester (Book collections on Project MUSE., 2019)
No contemporary development underscores the transnational linkage between the United State and Spanish-language America today more than the wave of in-migration during the 1980s and 1990s. This development, among others, has made clear what has always been true, that the United States is part of Spanish-language America. Translation and oral communication from Spanish to English have been constant phenomena since before the annexation of the Mexican Southwest in 1848. The expanding number of counternational translations from English to Spanish of Latinx fictional narratives by mainstream presses between the 1990s and 2010 is an indication of significant change in the relationship. A translational turn explores both the historical reality of Spanish-to-English translation and the "new" counternational English-to-Spanish translation of Latinx narratives. More than theorizing about translation, this book underscores long-standing contact, such as code-mixing and bi/multilingualism, between the two languages in US language and culture. Although some political groups persist in seeing and representing the US as having a single national tongue and community, the linguistic ecology here and in the global world is bilingualism and multilingualism